Beyond self-management: Physical activity as the main predictor of quality of life in older adults with hypertension in indonesia - Treesia Sujana; Galuh Chandra Irawan; Lidya Maryani; Ria Angelina (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Evidence shows family support, motivation, and physical activity are crucial for quality of life in elderly individuals with hypertension, with physical activity showing strong correlation. Factors like self-management, education, and income also play key roles. This study is situated in a Bandung City district where in 2021, primary hypertension was the leading cause of death and most prevalent disease. In 2023, of 437 residents with hypertension, only 35 elderly individuals regularly monitored their condition at the district's Community Health Center. Purpose: To investigate how physical activity and self-management affect quality of elderly life with Hypertension at a Community Health Care facility in an urban district in Bandung. Method: The study population included 72 elderly individuals, with a sample of 62 respondents determined by Slovin formula. Respondents were assessed using the SF36 questionnaire for quality of life, Physical Activities Scale for the Elderly (PASE), and Hypertension Self-Management Behavior Questionnaire (HSMBQ). Data analysis was conducted using multiple logistic regression. Results: Findings showed 69.4% of respondents had satisfactory physical activity levels, 56.5% showed effective self-management, and 83.9% reported high quality of life. Physical activity had the strongest influence (OR= 4.980) (95% CI OR: 7.520 – 211.29), while self-management showed moderate impact (OR=1.811). Conclusions: Elderly individuals with unsatisfactory physical activity face a 4,980-fold increased risk of declining quality of life compared to those with good activity levels. Those with unsatisfactory self-management face 1,811-fold increased risk of decreased quality of life versus those with effective practices.